STRATEGI MENINGKATKAN PENGAMALAN AJARAN ISLAM SISWA MELALUI BUDAYA RELIGIUS DI SEKOLAH BERBASIS PESANTREN - Muzammil Muzammil; Zamzamiyatus Zahro (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2026)
ABSTRACT Religious culture has become a strategic approach in Islamic education to strengthen students' character amid the challenges of globalization, rapid digital technological advancement, and changing youth behavior. This study aims to analyze the implementation of religious culture, the strategies employed, and their impact on improving students' practice of Islamic teachings at MA Misbahul Hidayah. The study employed a qualitative approach using a case study design. Data were collected through observations, in-depth interviews with the principal, Islamic Religious Education teachers, Islamic boarding school caregivers, and students, as well as documentation of religious activities and other supporting records. The data were analyzed interactively through the stages of data reduction, data display, and conclusion drawing, while data trustworthiness was ensured through source triangulation, technique triangulation, and member checking. The findings indicate that religious culture is implemented in an integrated manner through the habituation of worship, teachers' role modeling, and a supervision system integrated with the daily life of the Islamic boarding school. These strategies contributed to an increase in students' participation in congregational prayers from 72% in 2023 to 96% in 2025, accompanied by a significant decrease in disciplinary violations. The findings demonstrate that the integration of habituation, role modeling, and supervision effectively facilitates the internalization of Islamic values, transforming religious practice from a formal obligation into a genuine spiritual need. This model of religious culture offers an alternative framework for strengthening character education in Islamic boarding school-based educational institutions as well as other Islamic schools. ABSTRAK Budaya religius menjadi salah satu pendekatan strategis dalam pendidikan Islam untuk memperkuat karakter peserta didik di tengah tantangan globalisasi, perkembangan teknologi digital, dan perubahan perilaku generasi muda. Penelitian ini bertujuan menganalisis implementasi budaya religius, strategi yang diterapkan, serta dampaknya terhadap peningkatan pengamalan ajaran Islam siswa di MA Misbahul Hidayah. Penelitian menggunakan pendekatan kualitatif dengan jenis case study. Data diperoleh melalui observasi, wawancara mendalam dengan kepala madrasah, guru Pendidikan Agama Islam, pengasuh pesantren, dan siswa, serta dokumentasi kegiatan keagamaan dan data pendukung lainnya. Analisis data dilakukan secara interaktif melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan, sedangkan keabsahan data diuji menggunakan triangulasi sumber, triangulasi teknik, dan member checking. Hasil penelitian menunjukkan bahwa budaya religius diimplementasikan secara terpadu melalui pembiasaan ibadah, keteladanan pendidik, serta sistem pengawasan yang terintegrasi dengan kehidupan pesantren. Strategi tersebut berkontribusi terhadap peningkatan partisipasi salat berjamaah dari 72% pada tahun 2023 menjadi 96% pada tahun 2025, disertai penurunan pelanggaran kedisiplinan siswa. Temuan ini menunjukkan bahwa integrasi pembiasaan, keteladanan, dan pengawasan mampu mendorong proses internalisasi nilai-nilai Islam sehingga pengamalan ajaran agama berkembang menjadi kebutuhan spiritual, bukan sekadar pemenuhan kewajiban formal. Model budaya religius yang diterapkan berpotensi menjadi alternatif penguatan pendidikan karakter bagi lembaga pendidikan berbasis pesantren maupun sekolah Islam lainnya.